Post-modernism in the works of J. Fowles and I. Murdoch - Guzal Solieva (Zien Journals, 2022)
This article is dedicated to the Iris Murdoch and John Fowles works. The creative method of Iris Murdoch and John Fowles fully reflects in modernist (existential) tradition, and with the more distant Victorian, Gothic, detective novels. John Fowles' novels are often attributed to postmodern literature, but although the writer himself does not deny the influence of modern literary and philosophical trends on his work, he strongly emphasizes the connection with the realistic tradition of European literature. The specificity of Iris Murdoch’s novel heritage also makes it necessary to recognize the syncretism of her creative pursuits: her works contain features of the detective genre, Gothic, romanticism and psychological realism.
Keywords: post-modernism; literature; influence; novel